Systematics of the broad-nosed bats, Platyrrhinus umbratus (Lyon, 1902) and P. nigellus (Gardner and Carter, 1972) (Chiroptera: Phyllostomidae), based on genetic, morphometric, and ecological niche analyses. Issue 1 (30th November 2018) - Velazco, Paúl M.; Guevara, Lázaro; Molinari, Jesús
ABSTRACT: Platyrrhinus is a genus of leaf-nosed frugivorous bats that are endemic to the Neotropics. P. umbratus occurs in the Andean and costal mountain systems of Venezuela and Colombia. P. nigellus occurs along the Andes from Venezuela to Bolivia. Both species are medium-sized members of the genus possessing confusing taxonomic histories that have never intersected. Four of the 21 recognized species of Platyrrhinus, among them P. umbratus, do not have their taxonomic identification confirmed by molecular analyses. We provide the first genetic data (Cyt -b and ND2 sequences) for the species. Phylogenetic analyses including the new genetic data lead to the conclusion that P. umbratus and P. nigellus are conspecific. Through the use of Principal Components Analysis (PCA) and Ecological Niche Modeling (ENM), we confirm that P. umbratus and P. nigellus share high morphometric and environmental similarities. Based on such integrative approach, we regard P. nigellus as a junior synonym of P. umbratus . We provide an emended diagnosis of P. umbratus (subsuming P. nigellus ) and draw morphological comparisons with other species of the genus with which it is sympatric. The conservation status of P. umbratus needs to be determined. The high rate of habitat destruction in the tropical Andes may soon cause P. umbratus to be reassigned to the Near-Threatened (NT) category of the International Union for Conservation of Nature (IUCN).